PENGALIHAN UTANG: SOLUSI ATAS BEBAN UTANG LUAR NEGERI INDONESIA? - Murti, Gita Loka (UI Scholars Hub, 2002)
This paper discusses the mechanism underwhich Indonesian foreign debt is to be converted. It first traces the history of the idea of debt conversion, and the practice of it, mainly related to the underdeveloped countries' incapabilities to pay their debts, or countries-in-crises incapable of fulfilling its obligation. The history of Indonesian foreign debt is also traced arriving at its present condition with the proposition of debt conversion, mainly to environmental program. This paper also gives the insight on how the debt conversion scheme can be either a helping hand or a disaster to the country's economic condition. A helping hand, for it usually asks for lower value of debt's fulfillment and a program that helps the needy country restoring its environmental condition. A disaster, for its role as an instrument of the creditor's country to intervene in national matters of the debtors. Other scheme for decreasing Indonesian foreign debt is also considered in this paper